2014
DOI: 10.1111/ahe.12142
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Blood Vascular System in Veterinary Medicine

Abstract: Traditional veterinary anatomical models describe the branches of the caudal gluteal artery as the iliolumbar, cranial gluteal, lateral caudal, satellite of the ischiatic nerve and dorsal perineal arteries. However, some classical veterinary anatomy textbooks often indicate variations the general organization of the arterial tree, without giving any pattern of origin or illustrations of the different branching. The aim of this study was to investigate the presumptive variability of the caudal gluteal artery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The dorsal perineal artery is said to arise from the caudal gluteal artery within the ischiorectal fossa and supply blood to the skin and adipose tissue of the perineal region, while the ventral perineal artery arises from the internal artery and supplies the ventral part of the perineal region. A wide variety of vascular variations have been described for the IIA of male and female dogs including vascular variations for the perineal arteries [ 1 , 2 , 3 ]. However, detailed information about the corresponding innervation of these arteries is limited.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The dorsal perineal artery is said to arise from the caudal gluteal artery within the ischiorectal fossa and supply blood to the skin and adipose tissue of the perineal region, while the ventral perineal artery arises from the internal artery and supplies the ventral part of the perineal region. A wide variety of vascular variations have been described for the IIA of male and female dogs including vascular variations for the perineal arteries [ 1 , 2 , 3 ]. However, detailed information about the corresponding innervation of these arteries is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown anatomical variations in the caudal gluteal and internal pudendal arteries and their branches [1,2]. To evaluate the presumptive variations of the IIA in dogs, Avedillo et al [1][2][3] established a model of the general organization and distribution of the canine IIA using the guidelines established by the Nomina Anatomica Veterinaria [4]. The model was based on an "official illustration" made by Paul Simoens [5] and was designed to be easily followed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations